Health, Disease, and Social Structure in Rural India - Nanjunda, Devajana Chinnappa (Journal of Health and Allied Sciences NU, 2019)
Health and disease are the two noteworthy dimensions of behavior. During the lifetime, every individual traverses through health and disease. It is not an all or none type of occurrence but a relative location that explains whether the individual is healthy or unhealthy. The individual perception of health status is largely a psychological phenomenon. In spite of the beginning of the disease process, an individual may not even perceive it at any point of time. An organic disorder may not at all involve an individual until it is perceptible. Conversely, without any organic disorder, an individual may report himself to be unhealthy. Thus, logically, disease and health may coexist in the same individual. These two are not just equally exclusive entities. This study has been performed with two objectives (1) to study the changing social, economical, cultural, political, health, and demographic profile of the studied rural population and (2) to understand the changing illness ideology of the rural people and to find out the existing perception, health-seeking behavior, and culturally bounded attitudes about the onset of certain common diseases, and use of different systems of medicines. This study has been done in the selected districts on 800 households of Karnataka, India, using both qualitative and quantitative techniques.
Keywords: health; rural; culture; social; illness